Effect of dwell time during heat setting treatment on the properties of dyed and undyed knitted polyester fabrics / Nilam Khairunnisa Salina Kazaruddin - Kazaruddin, Nilam Khairunnisa Salina (Faculty of Applied Sciences, 2018)
Heat setting is a thermal treatment that involves heat, pressure and time to improve fabric dimensional stability and mechanical properties. However, some physical properties also may affected by the heat setting treatment. Thus, a study was conducted to find the effect of dwell time on the properties of dyed and undyed knitted polyester fabric. Knitted polyester fabric has lower stability than woven fabrics usually undergoes heat setting treatment to improve its dimensional stability. Meanwhile, dyed fabric also tends to fade its colour after heat setting treatment. Heat setting was done onto dyed and undyed knitted polyester fabrics bought at Spotlight Store Sdn Bhd at constant temperature of 160˚C at different dwell time of 3 minutes, 5 minutes and 7 minutes. Analysis on the mechanical properties, physical properties, colour fastness and whiteness index on both fabrics were done to observe if there was any effect caused by different dwell time. The results show that there were no significant results of different dwell time during heat setting treatment that may affect knitted fabrics‟ mechanical and physical properties. Fabrics that were bought at stores are likely to have already undergo treatment before they are sold to the consumers. Future researches can perform better analysis on the performance of the heat setting treatment by doing it on the untreated fabric sample.